Membaca Ulang Kejadian 3 dalam Bingkai Tafsir Poskolonial sebagai Respons terhadap Kerusakan Ekologi - Agustina Pasang; Shendy Carolina Lumintang (THRONOS: Jurnal Teologi Kristen, 2023)
This article aims to reveal the response according to the postcolonial interpretation of Genesis 3 to ecological oppression. This study used a qualitative research approach with content analysis method. Based on this study method a response was found that the postcolonial interpretation views crises or various ecological problems as a total human failure, not the result of sin. Human failure in question is an error in managing and being responsible for nature. This is of course a common concern that sin is not the root cause of human actions, but only a mistake manifested in the destruction of nature.